Pemahaman Teknologi Informasi, Motivasi Ekonomi, Disiplin Kerja, dan Pengaruhnya terhadap Kinerja Karyawan pada Bank Swasta di Kudus - Rina Fiati; Nafi' Inayati Zahro (Jurnal Sains dan Teknologi, 2011)
The purpose of this study is to investigate and to analyze the understanding factors of information technology, economic motivation, work discipline and its influence on employee performance of private bank in Kudus. The method used in this research is multiple linear regression analysis. The results of this study suggest that an understanding of information technology affects the employee performance of the private bank in Kudus. This is indicated by the significance value 0.024 is less than 0.05. This means that the first hypothesis is accepted.Economic motivation also affects the employee performance. Significance value 0.009 smaller than 0.05. This means that the second hypothesis is also accepted. Likewise, the third hypothesis, the significant value of the work discipline is 0.011. Therefore, the conclusion from this study is that both are either simultaneously or partially, variable understanding of information technology, economic motivation, and work discipline affect the employee performance of private bank in Kudus.